Three dimensional finite element analysis of the pediatric lumbar spine. Part II: biomechanical change as the initiating factor for pediatric isthmic spondylolisthesis at the growth plate - Sairyo, Koichi (Springer-Verlag, 2006)
A non-linear 3-dimensional finite element pediatric lumbar spine model with vertebral growth plate and apophyseal bony ring was developed. Lumbar spondylolysis was simulated in the model. The Von Mises stresses in the structures surrounding the vertebral growth plate, including apophyseal bony ring and osseous endplate were calculated in various loading modes. Instantaneous axis of rotation (IAR) path from flexion to extension was also analyzed. The results were compared with those of the intact model and the literature. The IAR path was at the posterior disc-endplate space of the lower vertebra in the intact spine, and moved cranially towards the upper-posterior disc space in the lytic spine. This was in agreement with in vivo radiological data by Sakamaki et al. [19]. During various loading modes, stresses in the spondylolytic pediatric model were higher than that of the intact model; ranging from 1.1 to 6.0 times, with the highest value in extension at the growth plate. In conclusion, FE models indicate that stress concentrations in the lytic model increase at the growth plate which may lead to physis stress fracture leading to spondylolisthesis.